THE STRATEGY OF HEALTH OFFICE IN EFFORTS TO OVERCOME STUNTING PREVALENCE IN TODDLERS IN SUMEDANG REGENCY IN 2022 - Afriani , Dini; Budianto, Dessy (PHSAJ - Public Health Sebelas April Journal, 2022)
Stunting is a poor condition related to nutrition caused by a lack of nutritional intake for a long period of time due to the provision of food that is not in accordance with nutritional needs. Purpose of Research for analyze the Strategy of the Health Office in Efforts to Overcome Stunting Prevalence in Toddlers in Sumedang District in 2022. This research was conducted at the Sumedang District Health Office using a qualitative method with a descriptive approach. Using the Non Probability Sampling technique with the Purposive Sampling method with a sample of 3 informants. Based on interviews that the Strategy of the Health Service in an effort to overcome the prevalence of stunting in children under five in Sumedang Regency is quite good. This is evidenced by the prevalence of stunting in the Sumedang Regency which has decreased every year. Sumedang Regency has so far been quite optimal in implementing the 8 convergence of stunting handling, this is seen in terms of organizational strategy, program strategy, and resource support strategies carried out. The advice that can be given is that the Health Office is always committed to implementing its strategies related to stunting prevention in accordance with applicable local government regulations